Figs S1–S3: Effects of melt-percolation, refertilization and deformation on upper mantle seismic anisotropy: constraints from peridotite xenoliths, Marie Byrd Land, West Antarctica - V. Chatzaras (6311636); S.C. Kruckenberg (6311642) (2021)
Examples of mantle xenoliths from Fosdick Mountains, Marie Byrd Land (S1), crystallographic orientations of olivine, orthopyroxene and clinopyroxene (S2) and variation of olivine, orthopyroxene and clinopyroxene CPO strength with temperature (S3)